GnRHa trigger-the story of the ugly duckling - Peter Humaidan, D.M.Sc; Thor Haahr, Ph.D (Elsevier, 2023)
The objective of this invited review is to describe the introduction and development of the GnRH agonist (GnRHa) trigger protocol in modern in vitro fertilization, focusing on ovarian hyperstimulation syndrome (OHSS) prevention and, equally important on the role of GnRHa trigger as an opener of the luteal phase "black box."The GnRHa trigger and freezing of all embryos is the ultimate weapon against OHSS in the OHSS-risk patient. In the non OHSS-risk patient, GnRHa trigger followed by a modified luteal phase support with lutein hormone activity and subsequent fresh embryo transfer results in excellent reproductive outcomes. Thus, the GnRHa trigger has paved the way for a virtually OHSS-free clinic, and equally important is the fact that the early lessons learned from studying the GnRHa trigger opened the "black box" of the luteal phase enabling improved reproductive outcomes in both fresh and frozen embryo transfer cycles.